2008
DOI: 10.1001/archinte.168.18.2022
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Consumption and the Risk of Breast Cancer in a Large Prospective Cohort of Women

Abstract: Background: Prospective data relating caffeine consumption to breast cancer risk are limited.Methods : We evaluated the association between caffeine consumption and breast cancer risk in women enrolled in a completed cancer prevention trial. Detailed dietary information was obtained at baseline (1992)(1993)(1994)(1995) from 38 432 women 45 years or older and free of cancer. During a mean follow-up of 10 years, we identified 1188 invasive breast cancer cases.Results: Consumption of caffeine and caffeinated bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 53 publications
3
49
4
Order By: Relevance
“…9 No association between tea and risk of breast cancer was observed in the Nurses’ Health Study 11 or in the Women’s Health Study. 10 Although there was no association with breast cancer overall or with ER+/PR+ breast cancer in our study, there was a nonsignificant positive association of heavy tea consumption with postmenopausal breast cancer (IRR=1.44, 95% CI 0.89–2.34, for ≥4 cups/day compared with none). Relatively few women frequently drank tea, and power was therefore limited for detecting a modest association.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…9 No association between tea and risk of breast cancer was observed in the Nurses’ Health Study 11 or in the Women’s Health Study. 10 Although there was no association with breast cancer overall or with ER+/PR+ breast cancer in our study, there was a nonsignificant positive association of heavy tea consumption with postmenopausal breast cancer (IRR=1.44, 95% CI 0.89–2.34, for ≥4 cups/day compared with none). Relatively few women frequently drank tea, and power was therefore limited for detecting a modest association.…”
Section: Discussioncontrasting
confidence: 81%
“…11 Among postmenopausal women in our study, we observed a similar magnitude of association for coffee that was not significant (IRR=0.85, 95% CI 0.55–1.32, for ≥4 cups/day relative to none), but there was no association between caffeine intake and breast cancer. Half of the women in our cohort rarely drank coffee, and their levels of caffeine consumption are lower than that reported in studies comprised mostly of white women, 10, 11 among whom coffee and caffeine intake would tend to be more highly correlated than among African-American women.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…By study design, 10 case–control studies [9], [21], [22], [32][38] and 16 prospective cohort studies [10][16], [20], [24][31]. By geographic region, 12 studies were conducted in Europe [9], [12], [14], [16], [22], [24], [25], [28], [30], [34]–[36], 11 in the United States [10], [11], [13], [15], [20], [21], [26], [31], [32], [37], [38] and 3 in Asia [27], [29], [33]. One study [24] only adjusted for age, whereas the other 25 studies adjusted for a wide range of potential confounders for breast cancer, including age, BMI, family history of breast cancer, smoking, alcohol, geographic area, parity, age at first birth, age at menarche and menopause, oral contraceptive and other female hormone use.…”
Section: Resultsmentioning
confidence: 99%